PERSEPSI SISWA TERHADAP IMPLEMENTASI PENDIDIKAN LINGKUNGAN HIDUP KELAS V SDN NO 166 INPRES BONTORITA DI KABUPATEN TAKALAR (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the perceptions of fifth-grade students regarding the implementation of environmental education in elementary schools. The focus of the study includes students’ understanding of environmental topics, their attitudes toward learning activities, and the application of environmentally friendly behaviors in daily school life. The research employed a descriptive qualitative approach, with data collected through observation, questionnaires, and interviews with fifth-grade students. The findings indicate that most students responded positively to the implementation of environmental education. Students were aware of the benefits of environment-related activities, such as maintaining school cleanliness and participating in environmental care programs. However, the understanding and application of environmentally responsible behavior among some students still need to be improved to ensure sustainability. Based on the results, it can be concluded that students’ perceptions of the implementation of environmental education in Grade V at SDN No. 166 Inpres Bontorita tend to be positive. These findings suggest that environmental education has been understood and its benefits have been experienced by students, although further efforts are required to strengthen its practical application.